New stratigraphic and geochemical data on the Holocene environment and climate from a tufa deposit at Direndall (Mamer Valley, Luxembourg). (July 2015) - Dabkowski, Julie; Brou, Laurent; Naton, Henri-Georges
Tufa deposits are proven to record high quality palaeoenvironmental and palaeoclimatic information. They also appear to be influenced by human activities as indicated by the 'late Holocene tufa decline' observed in Europe from the Atlantic optimum, when tufa should be well developed regarding climatic conditions. The studied tufa comes from the Mamer Valley in Luxembourg: Direndall. As it covers a broad part of the Holocene, this deposit offered a great opportunity to discuss modalities and timing of the tufa decline and the human impact on fluvial formations since the early Holocene. Recent fieldwork at Direndall allowed the collection of new stratigraphic data and samples for a geochemical study. We investigate calcite stable isotopes as records of past temperature and humidity conditions. Comparisons with the environmental reconstructions from a previous malacological study show strong consistency with the δ 13 C record and suggest humidity might have been the main factor controlling environment evolution at Direndall. Despite the climatic variations observed, none explains the environmental change towards open conditions while optimum forest develops as recorded by molluscs at the top of the sequence. This episode is likely to be linked to local anthropogenic forest clearance during the Roman occupation. However, no clear impact of human activity has been observed in the tufa stratigraphy or precipitation rate. The exceptionally long Direndall tufa sequence thus provided outstanding palaeoenvironmental and palaeoclimatic data and might become, together with the underlying fluvial and colluvial deposits, a reference site for the Holocene and Tardiglacial in Luxembourg and surrounding areas.